2009
DOI: 10.1016/j.smallrumres.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sources of vegetable fats on performance of dairy ewes and conjugated linoleic acid (CLA) in milk

Abstract: ARTICLE INFO ABSTRACT Keywords:Vegetable fats Milk performance Milk CLA Dairy eweTwo experiments were carried out to study the effects of supplementing the ration of lactating ewes with vegetable fats (sunflower oil, SO or hydrogenated palm oil, HPO; HIDROPALM®) on diet digestibility, milk yield and milk composition, and on the concentration of the conjugated linoleic acid (CLA) C18:2 cis-9 trans-11 and C18:l trans-11 (vaccenic acid, VA) and other main fatty acids in milk fat. Treatments involved a control die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
3
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 47 publications
7
47
3
16
Order By: Relevance
“…The more evident increase when RS was supplemented might result from its higher linoleic acid content in comparison with LS. Also in experiments by Castro et al (2009) the supplementation of soybean oil, rich in linoleic acid, to ewe diets increased the C18:2 c9 t11 CLA content by 29% in comparison with the control diet. Milk from ewes fed the sunflower seed diet contained more C18:2 c9 t11 CLA and less C18:3 c9 c12 c15 than milk from ewes fed the flaxseed diet (source of linolenic acid) (Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…The more evident increase when RS was supplemented might result from its higher linoleic acid content in comparison with LS. Also in experiments by Castro et al (2009) the supplementation of soybean oil, rich in linoleic acid, to ewe diets increased the C18:2 c9 t11 CLA content by 29% in comparison with the control diet. Milk from ewes fed the sunflower seed diet contained more C18:2 c9 t11 CLA and less C18:3 c9 c12 c15 than milk from ewes fed the flaxseed diet (source of linolenic acid) (Zhang et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…The inclusion of OLI, SOY and LIN increased the 18:0 content of the milk when compared with milk from PALM-fed ewes. This change results from the increased amounts of different C18 unsaturated fatty acids supplied by the oils, which can be completely hydrogenated in the rumen to 18:0 (Dhiman et al, 2000;Castro et al, 2009). The oil given to PALM-fed ewes has greater levels of 16:0 than the other oils, which is reflected in the composition of their milk .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, SOY-fed ewes displayed a nearly five-fold higher proportion of cis-9, trans-11 CLA than PALM-fed animals. A decrease in medium-chain FAs (C12 to C16) and SFA was also observed, and de novo synthesis of SFA may have been inhibited by the presence of long-chain FAs in the diet (Bouattour et al, 2008;Gó mez-Cortes et al, 2008b;Castro et al, 2009). Using SOY in feed has been proposed as an alternative for producing milk and dairy products enriched in MUFA, cis-9, trans-11 CLA and trans-11 18:1 (Bouattour et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research in dairy ewes (Gómez-Cortés et al, 2008;Castro et al, 2009) and steers (Ludden et al, 2009) has shown that diets supplemented with moderate amounts of unprotected oils modify the FA profile of milk and meat without adverse effects on digestion and animal performance. Hydrogenated palm oil (HIDROFAT) is a solid fat, inert in the rumen, made up of FAs of palm oil that undergo a process of hydrogenation, during which their degree of saturation increases.…”
Section: Introductionmentioning
confidence: 99%